2002
DOI: 10.1177/001316402128775021
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability Generalization Study of the Marlowe-Crowne Social Desirability Scale

Abstract: A reliability generalization (RG) study was conducted for the Marlowe-Crowne Social Desirability Scale (MCSDS). The MCSDS is the most commonly used tool designed to assess social desirability bias (SDB). Several short forms, consisting of items from the original 33-item version, are in use by researchers investigating the potential for SDB in responses to other scales. These forms have been used to measure a wide array of populations. Using a mixed-effects model analysis, the predicted score reliability for ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 8 publications
0
63
0
4
Order By: Relevance
“…Internal consistency was .63 indicating that it may not be acceptable. However, studies have consistently found lower reliabilities on this scale among males (Beretvas et al 2002). A sum score was computed so that higher scores on this scale would reflect a greater tendency to respond in socially desirable ways.…”
Section: Methodsmentioning
confidence: 97%
“…Internal consistency was .63 indicating that it may not be acceptable. However, studies have consistently found lower reliabilities on this scale among males (Beretvas et al 2002). A sum score was computed so that higher scores on this scale would reflect a greater tendency to respond in socially desirable ways.…”
Section: Methodsmentioning
confidence: 97%
“…Some research indicated social desirability can be used as the standard measure to control whether questionnaire responses are biased by desirable responding by comparing the correlations between social desirability response tendencies and the score of focal scales. If the correlations is not substantial, the discriminant validity of focal scales is proved to be satisfactory [37][38][39][40].…”
Section: Marlowe-crowne Social Desirability Scalementioning
confidence: 99%
“…Means and standard deviations for internal consistency reliability coefficients versus test-retest reliability coefficients are also presented in Table 2. It has been noted that RG studies can employ a wide array of statistical methods when conducting the actual analyses, including multiple linear regression (Vacha-Haase, 1998), bivariate correlation , canonical correlation analysis (Vacha-Haase, 1998), analysis of variance (Caruso, 2000), and mixed-effects hierarchical linear modeling (Beretvas, Meyers, & Leite, 2002 [this issue]). However, several subscales generated the most reliable scores across studies, namely the three subscales of the PAQ and the Trust and Communication subscales of the IPPA.…”
Section: Resultsmentioning
confidence: 99%